2021
DOI: 10.1099/ijsem.0.004911
|View full text |Cite
|
Sign up to set email alerts
|

Mesonia hitae sp. nov., isolated from the seawater of the South Atlantic Ocean

Abstract: A Gram-negative, non-motile, non-spore-forming, aerobic and short rod-shaped bacterial strain R32T, was isolated from seawater of the South Atlantic Ocean. Strain R32T grew at 10–40 °C (optimum 28 °C), at pH 6.0–8.0 (optimum 7.0), and in the presence of 3–8 % NaCl (w/v) (optimum 5 %). Cells were oxidase- and catalase-positive. The 16S rRNA gene sequence of strain R32T shared the highest similarities with Mesonia oceanica (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Differential characteristics between strain MT50 T and its closely related strains Strains: 1, MT50 T (data from this study); 2, Mesonia ostreae KCTC 23500 T (data from this study and data indicated by * from[5]); 3, Mesonia algae KMM 3909 T (data from[3]); 4, Mesonia aquimarina IMCC1021 T (data from[7]); 5, Mesonia maritimus 15-S14-6 T (data from[8]; 6, Mesonia mobilis KMM 6059 T (data from[6]); 7, Mesonia sediminis MF326 T (data from[10]). All strains are negative for hydrolysis of starch and positive for oxidase and hydrolysis of Tweens 20 and 60.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Differential characteristics between strain MT50 T and its closely related strains Strains: 1, MT50 T (data from this study); 2, Mesonia ostreae KCTC 23500 T (data from this study and data indicated by * from[5]); 3, Mesonia algae KMM 3909 T (data from[3]); 4, Mesonia aquimarina IMCC1021 T (data from[7]); 5, Mesonia maritimus 15-S14-6 T (data from[8]; 6, Mesonia mobilis KMM 6059 T (data from[6]); 7, Mesonia sediminis MF326 T (data from[10]). All strains are negative for hydrolysis of starch and positive for oxidase and hydrolysis of Tweens 20 and 60.…”
mentioning
confidence: 80%
“…The genus Mesonia, belonging to the family Flavobacteriaceae [1], phylum Bacteroidota [2], was originally proposed by Nedashkovskaya et al [3] with the type species being Mesonia algae [3]. Currently, the genus Mesonia consists of 10 validly published species (https://lpsn.dsmz.de/genus/Mesonia) [4], which were isolated from seawater [5][6][7][8][9] or polymeric organic matter rich marine environments, such as seaweed and aquacultural environments [3,[10][11][12][13]. Members of Mesonia are characterized as aerobic or facultatively anaerobic, rod-shaped, non-flagellated bacteria, with menaquinone-6 (MK-6) as the predominant respiratory quinone [3].…”
Section: Introductionmentioning
confidence: 99%